Fabricating High Performance, Donor–Acceptor Copolymer Solar Cells by Spray‐Coating in Air. Issue 4 (5th February 2013) - Wang, Tao; Scarratt, Nicholas W.; Yi, Hunan; Dunbar, Alan D. F.; Pearson, Andrew J.; Watters, Darren C.; Glen, Tom S.; Brook, Andrew C.; Kingsley, James; Buckley, Alastair R.; Skoda, Maximilian W. A.; Donald, Athene M.; et al.
Abstract We report the fabrication of high performance organic solar cells by spray‐coating the photoactive layer in air. The photovoltaic blends consist of a blend of carbazole and benzothiadiazole based donor–acceptor copolymers and the fullerene derivative PC70BM. Here, we formulate a number of photovoltaic inks using a range of solvent systems that we show can all be deposited by spray casting. We use a range of techniques to characterize the structure of such films, and show that spray‐cast films have comparable surface roughness to spin‐cast films and that vertical stratification that occurs during film drying reduces the concentration of PCBM towards the underlying PEDOT:PSS interface. We also show that the active layer thickness and the drying kinetics can be tuned through control of the substrate temperature. High power conversion efficiencies of 4.3%, 4.5% and 4.6% were obtained for solar cells made from a blend of PC70BM with the carbazole‐based co‐polymers PCDTBT, P2 and P1. By applying a low temperature anneal after the deposition of the cathode, the efficiency of spray‐cast solar‐cells based on a P2:PC70BM blend is increased to 5.0%. Spray coating holds significant promise as a technique capable of fabricating large‐area, high performance organic solar cells in air.